High‐Performance Pure Water‐Fed Anion Exchange Membrane Water Electrolysis with Patterned Membrane via Mechanical Stress and Hydration‐Mediated Patterning Technique - Yeonjae Lee; Sungjun Kim; Yoseph Shin; Yeram Shin; Seongmin Shin; Sanghyeok Lee; Minseop So; Tae‐Ho Kim; Sehkyu Park; Jang Yong Lee; Segeun Jang (Advanced Science)
Abstract Despite rapid advancements in anion exchange membrane water electrolysis (AEMWE) technology, achieving pure water‐fed AEMWE remains critical for system simplification and cost reduction. Under pure water‐fed conditions, electrochemical reactions occur solely at active sites connected to ionic networks. This study introduces an eco‐friendly patterning technique leveraging membrane swelling properties by applying mechanical stress during dehydration under fixed constraints. The method increases active sites by creating additional hydroxide ion pathways at the membrane‐electrode interface, eliminating the need for additional ionomers in the electrode. This innovation facilitates ion conduction via locally shortened pathways. Membrane electrode assemblies (MEAs) with patterned commercial membranes demonstrated significantly improved performance and durability compared to MEAs with conventional catalyst‐coated substrates and flat membranes under pure water‐fed conditions. The universal applicability of this technique was confirmed using in‐house fabricated anion exchange membranes, achieving exceptional current densities of 13.7 A cm−2 at 2.0 V in 1.0 M potassium hydroxide (KOH) and 2.8 A cm−2 at 2.0 V in pure water at 60 °C. Furthermore, the scalability of the technique was demonstrated through successful fabrication and operation of large‐area cells. These findings highlight the potential of this patterning method to advance AEMWE technology, enabling practical applications under pure water‐fed conditions.